ERA‐20CM: a twentieth‐century atmospheric model ensemble. (26th March 2015) - Hersbach, Hans; Peubey, Carole; Simmons, Adrian; Berrisford, Paul; Poli, Paul; Dee, Dick
<x xml:space="preserve">Abstract</x> This article describes an ensemble of ten atmospheric model integrations for the years 1899–2010, performed at the European Centre for Medium‐Range Weather Forecasts (ECMWF). Horizontal spectral resolution is T159 (about 125 km), using 91 levels in the vertical from the surface up to 1 Pa, and a time step of 1 h. This ensemble, denoted by ERA‐20CM, formed the first step toward a twentieth‐century reanalysis within ERA‐CLIM, a three‐year European funded project involving nine partners. Sea‐surface temperature and sea‐ice cover are prescribed by an ensemble of realizations (HadISST2), as recently produced by the Met Office Hadley Centre within ERA‐CLIM. Variation in these realizations reflect uncertainties in the available observational sources on which this product is based. Forcing terms in the model radiation scheme follow CMIP5 recommendations. Any effect of their uncertainty is neglected. These terms include solar forcing, greenhouse gases, ozone and aerosols. Both the ocean surface and radiative forcing incorporate a proper long‐term evolution of climate trends in the twentieth century, and the occurrence of major events, such as the El Niño–Southern Oscillations and volcanic eruptions. No atmospheric observations were assimilated. For this reason ERA‐20CM is not able to reproduce actual synoptic situations. However, the ensemble is able to provide a statistical estimate of the climate. Overall, the temperature rise over land is in fair agreement with the CRUTEM4 observational product. Over the last two decades the warming over land exceeds the warming over sea, which is consistent with models participating in the CMIP5 project, as well as with the ECMWF ERA‐Interim reanalysis. Some aspects of warming and of the hydrological cycle are discerned, and the model response to volcanic eruptions is qualitatively correct. The data from ERA‐20CM are freely available, embracing monthly‐mean fields for many atmospheric and ocean‐wave quantities, and synoptic fields for a small, essential subset.